﻿Smithia yehii (Leguminosae, Papilionoideae), a new species from Taiwan - Chiu-Mei Wang; Chih-Yi Chang; Yen-Hsueh Tseng (PhytoKeys, 2022)
A new species of Smithia Aiton, S. yehii C.M.Wang, Chih Y.Chang & Y.H.Tseng, sp. nov. from the wetlands of Taiwan is reported in this article. This species was mistakenly identified as S. sensitiva Aiton, but can be distinguished by its pale yellow corolla (vs. vivid yellow), often smaller flowers and shorter style. There is also a color gradient on the adaxial surface of the leaflets between young and mature leaves. Surface sculpture of pollen of S. yehii has significantly larger perforations, and muri are wider than those of S. sensitiva. An identification key to the Smithia taxa of Taiwan and S. sensitiva is presented.